The flow-cytometric analysis of gastric mucosa in patients with peptic ulcer operation - Abdulhalim BAKİ; Yavuz TEKELİOKLU; Abdulkadir REİS; Sait KAPICIOĞLU (Turkish Journal of Gastroenterology, 2019)
-